Deer antler stem cell-derived exosomes: a regenerative medicine powerhouse from nature’s own repair kit - Liu, Xidong (Frontiers in Cell and Developmental Biology, 2026)
Exosomes are essential mediators of intercellular communication and, as such, have attracted considerable interest in regenerative medicine. Aantler stem cells (ASCs) have become the central candidate in the field of the periodic regeneration of the deer antlers-the only mammalian organ that can entirely regenerate; they have been found to inherit regenerative characteristics of their parent cells, combined with a low immunogenicity. This is a systematic review of the research advancements on ASC-Exos, including the following main aspects: At the technical level, it describes the isolation techniques (ultracentrifugation, size exclusion chromatography, immunoaffinity capture) and their principles, advantages and disadvantages and their identification methods: TEM (cup-shaped/spherical morphology), DLS (size distribution), Western blot (markers: CD63, CD81, TSG101); In the functional and mechanistic levels, through cargos (proteins, mRNAs, let-7a/let-7b), ASC-Exos enhance fibroblast proliferation/migration (CCK-8, Transwell), osteogenic genes expression (Runx2, Osterix) to differentiate into osteoblasts as well as controlling macrophage polarization (reduce TNF-α, IL-6; enhance IL-10); At the translational application level, ASC-Exos have been shown to be effective in bone repair (rat femoral defect, micro-CT/histology), cartilage protection (alleviate osteoarthritis), wound healing (mouse full-thickness wounds, angiogenesis), pulmonary fibrosis (inhibit CCL7-mediated monocyte-macrophage recruitment), tumor immunotherapy (engineered M2Pep/poly (I: C) ASC-Exos + PD-L1 antibodies suppress tumor growth/metastasis), treatment of neurodegenerative diseases, anti-aging and intervention in age-related diseases and treatment of metabolic disorders. Moreover, this review reveals the challenges in the contemporary research that are of critical importance: optimization of large-scale production and purification of ASC-Exos to provide uniformity in the clinical use; full clarification of the molecular processes that underlie ASC-Exos-mediated effects (e.g., metabolic reprogramming control in tumors); and the absence of detailed preclinical and clinical data on the long-term safety and efficacy. Finally, the review would serve as a valuable resource to developing fundamental research in the field of ASC-Exos and increasing the pace of its clinical application, especially when used together in conjunction with more sophisticated methods of drug delivery and tissue regeneration, to achieve new prospects in the treatment of incurable diseases and repair tissue in regenerative medicine.